Pengaruh Penggunaan QRIS terhadap Peningkatan Pendapatan UMKM di Desa Sukarara - Alpan Khoyali; Refreandi Haeri; Sanwani Sanwani (Tirai Edukasi : Jurnal Pendidikan, 2026)
This study aims to analyze the influence of using the Quick Response Code Indonesian Standard (QRIS) on the income improvement of Micro, Small, and Medium Enterprises (MSMEs) in Sukarara Village. QRIS is a digital payment system initiated by Bank Indonesia to facilitate cashless transactions. This research employed a quantitative approach through a survey method involving 30 MSME actors who have implemented QRIS. Data were collected using questionnaires and documentation, then analyzed using a paired t-test. The results indicate that QRIS usage has a positive and significant impact on MSME income improvement. QRIS facilitates transactions, increases customer numbers, and supports efficient financial recording. These findings highlight that payment digitalization through QRIS plays a crucial role in enhancing MSME competitiveness in rural areas and suggest the importance of improving digital literacy and supporting infrastructure.